Luke Jensen, bounty hunter - Johnstone, William W.; Johnstone, J. A. (Pinnacle, 2022)
The last days of the Civil War. Richmond is under siege. Confederate soldier Luke Jensen is assigned the task of smuggling gold out of the city before the Yankees get their hands on it. He is ambushed by four deserters, robbed, shot in the back, and left for dead. Taken in by a Georgia farmer and his beautiful daughter, Luke is nursed back to health. Though crippled, he hopes to reunite with his long-lost brother, Smoke, but a growing romance keeps him on the farm. Then ruthless carpetbaggers arrive and fate takes a tragic turn. Luke, driven by vengeance, becomes the greatest bounty hunter who ever lived.
Keywords: Soldiers; Bounty hunters; Revenge; Brothers; Reconstruction (U.S. history, 1865-1877); Southern States; United States -- History -- Civil War, 1861-1865; Western stories; War stories; Historical fiction; Large type books